Love and the Capacity to Love An Ontological Analysis of Love According to Ibn Sina and Thomas Aquinas - Albertus Joni (P3TK, Sanata Dharma University, 2020)
This paper will elaborate on the different concepts of love as offered by Thomas Aquinas and Ibn Sina; two prominent thinkers representing the Christian and Islamic tradition. Ris?lah f? al- ishq (The Treatise on Love) of Ibn Sina is comparable in terms of theological and philosophical approaches to the Aquinas treatment of love in Summa Theologiae II-IIae q.23, a.2. I argue that since Ibn Sinas ontological definition of love is related tightly to his cosmogony, then there is no rigid distinction between the love of the Pure Being and the contingent beings. Love acts as a medium of unification and perfection towards the Pure Being. The different levels of love are already determined in the contingent beings according to the principle of harmonia during the emanative process. For Aquinas, love is present only in the rational being as it is a grace of God, the Holy Spirit himself. But this similar notion of Aristotelian harmonia in Aquinas (1) would never be able to blur the wide, apparent discrepancy between God and human beings. (2) Through the model of rational love as an intellectual counsel, we can see that there is no sense of determinism on Aquinas concept of rational love.